GC-MS-based metabolic profiling of essential oils from Citrus paradisi, Lawsonia inermis, and Ruta graveolens and assessment of their acetylcholinesterase inhibitory potential - Amawi, Rema M.; Ashmawy, Naglaa S. (Frontiers in Chemistry, 2026)
IntroductionPlant-derived essential oils (EOs) are rich sources of bioactive compounds, some of which exhibit acetylcholinesterase (AChE) inhibitory activity and may offer therapeutic potential for the management of Alzheimer’s disease (AD). This study aimed to evaluate the chemical composition and AChE inhibitory potential of essential oils extracted from Citrus paradisi (grapefruit), Lawsonia inermis (henna), and Ruta graveolens (sadab).MethodsEssential oils were obtained by hydrodistillation and analyzed using gas chromatography–mass spectrometry (GC–MS) to identify their chemical constituents. AChE inhibitory activity was determined using Ellman’s colorimetric assay, and IC50 values were calculated to assess inhibitory potency.ResultsA total of 63 metabolites were identified across the three essential oils, accounting for approximately 90% of their total composition. Grapefruit EO was predominantly composed of limonene (89.94%), henna EO was rich in phytol (41.42%) and limonene (23.02%), while sadab EO was characterized by 1-hexadecanol acetate (26.39%) and phytol (20.54%). Grapefruit EO exhibited the strongest AChE inhibitory activity (IC50 = 12.62 ± 0.48 μg/mL), followed by henna EO (IC50 = 43.90 ± 0.97 μg/mL), whereas sadab EO showed negligible inhibition.DiscussionThe notable AChE inhibitory activity observed in grapefruit and henna essential oils is likely attributable to their high terpenoid content. These findings suggest that selected plant-derived essential oils may represent promising natural candidates for the prevention or management of neurodegenerative disorders such as Alzheimer’s disease.